Beyond viral : how to attract customers, promote your brand, and make money with online video - Nalty, Kevin H. (New rules of social media series., 2010)
"Promote your product using the most visceral form of social media-online video. Learn how to create cost-effective videos, engage your customers, compel them to measurable behaviors (awareness, intent, and purchase), and sustain your brand online. Beyond Viral gives you the tools and tricks to successfully use online video to reach your business goals"--Provided by publisher